THE ROLE OF LOCAL GOVERNMENT IN COMBATING PALM OIL PLANTATION THEFT: AN ANALYSIS OF REGULATIONS AND POLICIES - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2025)
Palm oil plantation theft is a serious problem that requires attention and action from local governments. This study aims to analyse the role of local governments in combating palm oil plantation theft through existing regulations and policies. The method used is qualitative descriptive analysis by reviewing various relevant regulations and policies. The results of the study indicate that local governments play a key role in combating oil palm plantation theft, but there is still room for improvement. Recommendations include enhancing coordination among stakeholders, strengthening law enforcement, empowering communities around plantations, and promoting sustainable development to address the root causes of the problem. With these strategic steps, it is hoped that palm oil plantation theft can be reduced and the welfare of communities around plantations can improve.